Food and museums - Levent, Nina Sobol, 1971-; Mihalache, Irina D., 1982- (Bloomsbury Academic, 2018)
"Museums of all kinds - art, history, culture, science centers and heritage sites - are actively engaging with food through exhibitions, collections, and stories about food production, consumption, history, taste, and aesthetics. Food also plays a central role in their food courts, restaurants, cafes, gardens, and gift shops. Food and Museums is the first book to explore the diverse, complex relationship between museums and food. This edited collection features theoretical analysis from cultural historians, anthropologists, neuroscientists, and food studies scholars; interviews with museum professionals, artists and chefs; and critical case studies from a wide range of cultural institutions and museums to establish an interdisciplinary framework for the analysis of the role of food in museums. Exploring the richness and complexity of sensory, cultural, social, and political significance of food today as well as in the past, the book demonstrates how food is changing the current museological landscape. A fascinating look at contemporary museums through the lens of food, this is an essential read for students and researchers in museum studies, food studies, cultural studies, and sensory studies as well as museum and food professionals"--Publisher description